A socio-institutional perspective on the reluctance among the elderly concerning the commercialization of 3D surgical video technology in Sweden - Pankaj Patel; Maj Stenmark; Vinit Parida; Phan-Kiet Tran (Journal of Innovation & Knowledge (JIK), 2023)
The pursuit of commercialization is at the core of economic activity, and limited commercialization success is generally ascribed to the lower scalability or potential of the venture. Drawing on the anti-profit-taking socio-institutional perspective and innovation resistance theory, commercialization of a value-creating technology could be resisted from the demand side. We use a 3D surgical video technology developed at a Swedish hospital along with Potentially All Pairwise RanKings of all possible alternatives (PAPRIKA) based on conjoint analysis completed by 1437 elderly individuals. We find that, despite the value benefits for the surgeon and the overall social benefits of the technology, the most preferred part-worth utility (i.e., weight) of relative importance is a preference for not commercializing the technology for profit. These findings carry implications for entrepreneurship and institutional theory related to medical innovations in countries with universal healthcare.
Keywords: I19; O30; O33; 650; Commercialization; Non-profit institutions; Universal healthcare